Leary site revisited: Oneota and Central Plains tradition occupation along the lower Missouri - Ritterbush, Lauren W. (My University, 2002)
Archaeologists of the central Plains and prairie peninsula have known of the Leary site (25RH1) in extreme southeastern Nebraska for more than 85 years. Early archaeological visitors to the site concluded that its remains were distinctly different than those from more common Central Plains tradition sites in the region. Instead, the Leary ceramics compare favorably with those from Oneota sites typically found to the east. The apparent anomalous position of this Oneota settlement in the central Plains indicates trans-Missouri movement of Oneota peoples into the eastern Plains. Leary is significant for the clues it holds regarding overall Oneota expansion during the Late Prehistoric period, as well as possible cultural interaction with Plains populations. The latter is especially relevant due to the fact that archaeological remains of the Central Plains tradition are also present at the Leary site. Analysis of curated assemblages collected during 1935 and 1965 suggests multiple Central Plains tradition occupations bracketing or overlapping those associated with the Oneota tradition. This and other finds at the Leary site raise interesting research questions to be addressed through future archaeological studies.
Keywords: Oneota; Central Plains tradition; Leary site